2020
DOI: 10.1002/1878-0261.12732
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers improve current prediction of metastasis development in early‐stage melanoma patients: a machine learning‐based study

Abstract: Metastasis development represents an important threat for melanoma patients, even when diagnosed at early stages and upon removal of the primary tumor. In this scenario, determination of prognostic biomarkers would be of great interest. Serum contains information about the general status of the organism and therefore represents a valuable source for biomarkers. Thus, we aimed to define serological biomarkers that could be used along with clinical and histopathological features of the disease to predict metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…In other studies, SVM effectively discriminated melanoma on the basis of dermoscopic images [44], ultrasonic and spectrophotometric images [45], BRAF status [46], or dermo-fluorescence spectra [47], with a reported accuracy up to 90%. SVM was previously used for prognostic purposes in melanoma patients [48] but, to our knowledge, the present study is the first applying the SVM analysis to cytokine/chemokine-expression values to discriminate melanoma from controls, both in serum and in tissue, in a large group of controls and patients. The SVM procedure was indeed able to improve the ability to classify the serum samples, from AUC = 0.70 for IL-6 expression (see Table 2) up to AUC = 0.761 for the combined indicators (see Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, SVM effectively discriminated melanoma on the basis of dermoscopic images [44], ultrasonic and spectrophotometric images [45], BRAF status [46], or dermo-fluorescence spectra [47], with a reported accuracy up to 90%. SVM was previously used for prognostic purposes in melanoma patients [48] but, to our knowledge, the present study is the first applying the SVM analysis to cytokine/chemokine-expression values to discriminate melanoma from controls, both in serum and in tissue, in a large group of controls and patients. The SVM procedure was indeed able to improve the ability to classify the serum samples, from AUC = 0.70 for IL-6 expression (see Table 2) up to AUC = 0.761 for the combined indicators (see Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…Initial evidence reported by Porter et al revealed that the protein was overexpressed in 10% of invasive breast carcinomas and conferred cell growth and survival, launching dermcidin as a candidate oncogene [ 51 ]. Thereafter, several research groups reported additional evidence concerning this protein in various types of cancers, as illustrated in Figure 7 : Intracellular or extracellular overexpression of dermcidin in breast cancer [ 52 ], gastric cancer [ 53 , 54 ], hepatocellular carcinoma [ 55 , 56 ], lung cancer [ 57 , 58 ], melanoma [ 59 , 60 ], and pancreatic cancer [ 61 ]; promotion of cell survival [ 48 , 51 , 62 , 63 , 64 ]; and promotion of cell migration [ 55 , 65 ]. Although there are solid data that link dermcidin and cancer, the proper role of the protein at molecular levels and its contribution to tumorigenesis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Dermcidin expression is higher in lung cancer patients compared with that in healthy subjects [26]. Among cutaneous malignancies, having high serum levels of dermcidin at the moment of melanoma diagnosis has been associated with the metastatic progression of melanoma among melanoma patients [27,28].…”
Section: Discussionmentioning
confidence: 99%